Successful Secondary Endovascular Intervention in Pediatric Patients with Venous Thromboembolic Events - Glonnegger, Hannah; Zieger, Barbara; Grohmann, Jochen; Freund, Gabriele; Zeller, Thomas; Uhl, Markus; Stiller, Brigitte (Hämostaseologie, 2022)
Background In the past, pediatric patients with venous thromboembolic events (VTE) were treated with low-molecular-weight heparin (LMWH) which was successful in around 70% of the cases. However, anticoagulation alone might not restore patency in all patients, and advanced therapeutic options to prevent postthrombotic syndrome are needed. During recent years, endovascular interventions have become a treatment option for pediatric patients with persistent thrombotic occlusion, not only in life- or limb-threatening VTE.Methods We evaluated 12 consecutive patients (11–17 years) with newly diagnosed VTE being treated at our department during the last 4 years (2017–2020). In case follow-up examination showed persistent venoocclusion under anticoagulation, patients received secondary interventional therapy like recanalization, percutaneous transluminal angioplasty with or without catheter-directed thrombolysis, and stenting. Patients with no clinical signs of venoocclusion or regredient thrombosis in imaging examination received anticoagulation alone.Results Six of 12 (50%) patients underwent catheter intervention. Median time from diagnosis to intervention was 4 months (0–12 months). Reintervention was necessary in one (8%) case and complete recanalization failed in one (8%) case. There were no major bleeding events or other major postinterventional complications, no acute or late local recurrence, and all patients reported clinical improvement after the procedure.Conclusion If endovascular intervention is used in teenage patients with persistent symptomatic VTE, reduction of postthrombotic symptoms is possible, even if intervention is performed secondary to failure of anticoagulation. Multidisciplinary treatment decisions can be based on the clinical course and follow-up imaging.
Keywords: endovascular intervention; children; venous thromboembolic event